Fitting different nonlinear growth models to oil palm (Elaeis guineensis) yield along the crop lifecycle, Costa Rica - Solórzano-Thompson, Johanna (2021)
This research focused on the oil palm crop in the southern zone of Costa Rica due to the high impact it generates on the economic development of Costa Rican farmers. The oil palm yield growth curve was adjusted along the crop life cycle, and the forecast efficiency of eight nonlinear growth models was compared based on different statistical criteria and normality tests. Then the Box-Cox transformation method was applied to correct the absence of normality.  The applied nonlinear models were adequate to forecast oil palm yield, and the Morgan-Mercer-Flodin model produced the best fit statistics. This research constitutes an input for plantation renovation practices, as well as the economic valuation of crops that may be pledged as collaterals.